Problems and Prospects of Development of Microfinance Organizations in the Russian Federation - V. A. Tsvetkov; M. N. Dudin; S. N. Saifieva (Финансы: теория и практика, 2019)
Intensive development of microfinance organizations in Russia has a double meaning. On the one hand, they are claimed by the population; on the other hand, the state control over their activities is difficult. The study reveals the nature, problems and prospects of development of microfinance organizations in Russia. The aim of the authors is to determine the nature of the controversial development of the financial market segment and suggest mechanisms that can resolve these contradictions. The study used a systematic approach and statistical methods. The authors analyzed analytical and statistical information of the Bank of Russia. The lack of adequate mechanisms for the state regulation and control over the activities of microfinance organizations the state is due to the gaps in the legislative framework. This was the reason for the increase in the share of overdue debts, the high debt load of the population, the intensification of collectors, the increase in lawsuits. The actions are proposed for increasing transparency of microfinance transactions without increasing the administrative burden on regulatory authorities. Among them are: attracting private investorslenders to microfinance activities with the development of Internet infrastructure, creating a special online platform to register microloan transactions between individuals and / or legal entities in real time with recording them in the Bank of Russia and in tax services. It is also necessary to amend the legislation on microfinance activity. This sequence of actions will lead to a reduction in the informal sector in the microfinance segment and in the financial market of the Russian Federation as a whole. The proposals made in the article can be used to develop the anti-crisis program of the Government of the Russian Federation in this area.